Olhar para domésticas e diaristas uma perspectiva sobre a saúde e condições de trabalho - Cardoso, Viviane de Freitas (Universidade Federal de São Carlos, 2023)
House cleaning is an important way for women to participate in the labor market. In Brazil, there are two types of cleaners: housekeepers receive monthly payment and house cleaners are paid by the day. The main objective of this thesis was to describe the sociodemographic, health and occupational profile of a sample of housekeepers and house cleaners in Brazil and how they were impacted by the COVID-19 pandemic. This investigation was based on two studies. Study I describe the sociodemographic, health and occupational profile of a sample of workers, a cross-sectional study that included 20 housekeepers and 29 house cleaners. House cleaners were younger, received lower wages, had longer daily working hours and had more homes to clean in comparison to housekeepers. The most reported health problems were obesity (56%), systemic arterial hypertension (47%) and spinal problems (34%). Musculoskeletal symptoms were frequent in the lower back and upper limbs. Around 51% reported the use of analgesics. The focus of Study II was to describe the differences that occurred in terms of the occupational and health profile of housekeepers and day laborers and how the pandemic influenced these changes from the perspective of the complexity paradigm. Data collected in 2018 and 2020, with triangulation of methods, 29 house cleaners participated. The changes caused by the pandemic in the work context were in terms of job losses, reduction in workload and on payment, especially for house cleaners. Housekeepers had to negotiate strategies such as advancing vacations or reducing working hours. Conflicts were identified regarding exposure and health care, reduction in the use of public transport. In personal life, the pandemic influenced social interaction and family dynamics and access to health care. This context is added to the changes that occurred in family dynamics. The results of this thesis show the vulnerability of this work category in terms of education level, workload, salary, health conditions and lack of social security. These changes aroused conflicts and reflections both in work relationships and in the perspective of exposure itself, pointing out how much this work is marked by challenges, vulnerabilities and invisibility.
Housekeepers and house cleaners: a perspective on health and working conditions
Keywords: Trabalho doméstico; Pesquisa qualitativa; Saúde do trabalhador; Sintomas musculoesqueléticos; Pandemia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL